Electronic Word of Mouth in Building Decisions To Invest in Mutual Funds Through Bibit.id - Febi Alfia Ulfa; Ari Susanti (Kanal: Jurnal Ilmu Komunikasi, 2023)
Financial stability is the dream of every human being in facing life future, in the midst of rapid economic progress that makes people innovate, one of which is by investing. A person's lack of knowledge investing results negative things that can affect investment decisions. Bibit, which’s an investment platform that’s great demand by the people of Indonesia, has made researchers interested in examining the activities that occur in the dissemination of information about Bibit investments. Electronic word of mouth which’s commonly known as e-WOM is one of the newest innovations in the world of digital marketing, known for its broad and effective dissemination of information, making e-WOM one of the reasons for researchers to get to know more about e-WOM in disseminating information to the Bibit community. This research focused on how dimensions of e-WOM in building an interest investing in Bibit mutual funds for novice investors and what’s the role of e-WOM in building investment decisions for novice investors through AIDDA theory. The purpose of this study to determine the activity of e-WOM carried out by the Bibit community to attract novice investors to invest in the Bibit.id. This study uses a qualitative descriptive method by collecting interview data online as well as the determination of informants using a purposive sampling technique. The results of this study indicate that there’s a positive role in making investment decisions the Bibit.id by novice investors, due to the activity of e-WOM in the Bibit community dissemination of information that supports investment decisions.